Generational mutation patterns in a honey bee Deformed wing virus via infectious clones - Anthony Nearman; Alriana Buller-Jarrett; Dawn Boncristiani; Eugene Ryabov; Yanping Chen; Jay D. Evans (PLoS ONE, 2025)
Efforts to improve honey bee colony health continue due to persistent high loss rates. A major focus in this area is Deformed wing virus (DWV), a key driver of colony loss. The application of modern molecular techniques has characterized the DWV genome and its high mutational rate that enables the formation of diverse quasi-species populations capable of evading host immune responses, while other work has led to the development of DWV clones suitable for sequence-specific tracking of viral dynamics. In this work we combine knowledge of these efforts to track the mutational progression in a DWV clone surrounding an area of low nucleotide diversity and compare it to its wild-type source. We achieve this through amplicon sequencing of the structural viral protein, VP2, after incubation across three generations and multiple host genetic sources. Inocula were injected into pupae, allowed to replicate, then extracted for a further two generations of injections. For the final injection generation, recipient pupae were injected with preparations from either the same genetic source or cross-fostered from other colonies. Overall, we compared the mean number and type of mutations, their proportional abundance in the read pool, and specific locations across strains. Sequencing results indicate a limited number of mutational hotspots, which were driven by silent mutations in the final injection generation of the wild-type strains. No significant differences were found among other mutation types, cross-fostering status, or interactions with host genetics. This work is an initial attempt at examining viral dynamics in a cloned system across multiple generations and treatment groups. The results provide valuable insights, which may further enhance our understanding of viral dynamics and potentially improve future honey bee therapeutics.